2020
DOI: 10.1111/ijd.15283
|View full text |Cite
|
Sign up to set email alerts
|

Melanomas of the scalp: is hair coverage preventing early diagnosis?

Abstract: Background Scalp melanomas are usually thicker and show worse prognosis than other sites and other head and neck melanomas. One hypothesis to explain this aggressive behavior could be diagnosis delay attributed to hair concealment of lesions. Methods Primary melanomas of the scalp diagnosed over two decades at four reference centers in Australia and Italy were included. Hair coverage and visibility of the lesions were assessed on preoperative photographic documentation by two investigators and correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…They usually coexist with benign and premalignant lesions, such as AKs, SLs and seborrheic keratoses (SKs), which can obscure the malignancy and contribute to delayed diagnosis. 8 One particular challenge of lentiginous melanomas of sun-damaged skin is their slow-growing nature, which often results in a large dimension upon detection. 5 An excisional biopsy is frequently not feasible or could cause significant morbidity and cosmetic disfigurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They usually coexist with benign and premalignant lesions, such as AKs, SLs and seborrheic keratoses (SKs), which can obscure the malignancy and contribute to delayed diagnosis. 8 One particular challenge of lentiginous melanomas of sun-damaged skin is their slow-growing nature, which often results in a large dimension upon detection. 5 An excisional biopsy is frequently not feasible or could cause significant morbidity and cosmetic disfigurement.…”
Section: Discussionmentioning
confidence: 99%
“…Most scalp melanomas arise on the bald and sun‐damaged scalp of elderly males, similarly to the case presented herein. They usually coexist with benign and premalignant lesions, such as AKs, SLs and seborrheic keratoses (SKs), which can obscure the malignancy and contribute to delayed diagnosis 8 …”
Section: Discussionmentioning
confidence: 99%
“…However, they added, when considering only the invasive cases, Breslow thickness was not different among different categories of hair coverage. Considering these results, Pereira et al 14 concluded that there are two different scenarios: Lentigo Maligna (LM) and non-LM subtype of SM. Elderly patients with androgenic alopecia and photodamage tend to develop LM type of melanoma, the melanomas are detected before becoming invasive because they appear on visible areas and are of a slow growing subtype.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…SM is associated with a greater risk of disease progression and death than melanoma in other sites [5][6][7][8][9][10] , likely due to hair coverage resulting in later diagnosis (Fig. 1) [11][12][13] , the high proportion of melanomas with rapid vertical growth 4,9 , the presence of melanomas in an area of higher blood and lymph supply 14,15 , and inadequate surgical margins (Fig. 2) 16 .…”
Section: Introductionmentioning
confidence: 99%